The roles of stakeholders in vocational education and training systems in times of digitalisation - a German-Swiss comparison (RADigital): Final report of the development project - Ute Hippach-Schneider; Elena Rieder (Bundesinstitut für Berufsbildung (BIBB), 2021)
In both Switzerland and Germany, stakeholders in vocational education and training (VET) are responding to the serious technological changes with numerous initiatives and programmes. This report examines the impact on the respective national governance structures and steering mechanisms by analysing the role of the actors and the form of their cooperation. It can be stated that despite many similarities between the systems, the differences in the distribution of state steering power, especially in the coordination of education policy decisions, are clearly noticeable in this context.
urn:nbn:de:0035-0895-8
Keywords: 370